1996
DOI: 10.1016/s0840-4704(10)60756-9
|View full text |Cite
|
Sign up to set email alerts
|

Downsizing in the Hospital System: A Restructuring Process

Abstract: In an effort to maintain fiscal viability, hospitals have been undergoing major restructuring. This article reports on a study that examined innovative downsizing strategies used by 20 acute care hospitals in Ontario. The study team reviewed hospital operating plans and analysed the results of interviews conducted with administrators and employees about the downsizing process. Results revealed no uniformity of approach to downsizing. Although many administrators expressed the need for a cooperative approach, d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2000
2000
2009
2009

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…These observations raise questions about the processes used to undertake restructuring within nursing. Baumann et al. (1996) identified that nurses expressed concern about their degree of involvement in decisions about their future employment settings.…”
Section: Staff MIX and Nurse Outcomesmentioning
confidence: 99%
“…These observations raise questions about the processes used to undertake restructuring within nursing. Baumann et al. (1996) identified that nurses expressed concern about their degree of involvement in decisions about their future employment settings.…”
Section: Staff MIX and Nurse Outcomesmentioning
confidence: 99%
“…Previous literature has recommended the use of the strategies either individually or in a combined approach as in the case of the PE model. 1,[4][5][6]11 McLellan et al investigated a similar multifaceted approach of educating and supporting nursing staff during an Ottawa hospital closure that showed promising results. 4,17 In addition, the authors showed that a communication strategy that was consistent and frequent was found to be quite successful and this is further supported by the current study.…”
Section: Discussionmentioning
confidence: 99%
“…ince the late '80s, hospitals worldwide have been closing. 1,2 In Canada, as a result of recent provincial health care restructuring, there have been hospital closures, particularly in Ontario, [3][4][5] British Columbia, 6 Saskatchewan 7 and Newfoundland and Labrador. 8 These closures have negatively affected staff and the community, for example, stress and burnout have been well documented in staff after a closure; [9][10][11] therefore, obtaining further input from these groups has been acknowledged.…”
mentioning
confidence: 99%
“…Instead, sites were selected where local restructuring decisions had been carried out, and the CEOs were approached because they had been closely involved in devising these local initiatives. Other studies have suggested that these types of local initiatives are less common in smaller community settings, especially those with only one hospital (e.g., Baumann et al 1996). A major reason for contacting these CEOs, therefore, was to find out more from them about why the hospital executive in these communities had chosen a more aggressive strategic response compared to other smaller hospitals in the province, and to recount their experiences in pursuing these initiatives.…”
Section: Restructuring Initiatives In Two 'Smaller' Urban Settings: Imentioning
confidence: 99%